Peran Kepemimpinan K.H. Hasyim Asy’ari dalam Resolusi Jihad - Muhlisin, Fathurijal; Huda, Khoerul (Prodi Pendidikan Agama Islam IAINU Kebumen, 2022)
Leadership is how a person is able to have an impact on someone so as to achieve the desired goal of the leader. Someone who was born in Gedang, East Java, who came from blue and white blood, was able to have such a big impact on the Indonesian nation, namely K.H.Muhammad Hasyim Asy'ari, he is someone who has a very high fighting spirit, especially in the role of fighting for Indonesian independence by risking wealth and even life. The purpose of this study is to find out how the figure of K.H. Hasyim Asy'ari has such a big role for the Indonesian people. In this study using library research methods or library research. Researchers will collect some data in the form of literature related to the figure of K.H.Hasyim Asy'ari who was very influential on the Indonesian nation through a review of books,notes, journals and other reports. Based on the research of K.H. Hasyim Asy'ari raised the fighting spirit of the Indonesian people by issuing a fatwa that jihad in the way of Allah is mandatory for Muslims, especially in defending independence. So that the fighting spirit ofFisabilliah arose which moved the Indongai community, groups such as Hezbollah, Sabililah,PETA, and Ulama.